The Role of School Well-Being on Student Engagement in Students of SMA Negeri 1 Polewali - Wahdania, Rifka; Akmal, Nur; Ahmad, Astiti Tenriawaru (Polteknik Ilmu Pemasyarakatan, 2025)
School is one of the environments that plays a role in shaping the character of students. If the school can meet the needs of students while they are there, then students will feel comfortable in school. This convenience will have an impact on their involvement in learning activities. The high well-being of students in school will affect their behavior in the classroom, known as student engagement. This study aims to determine how the role of school well-being on student engagement in SMA Negeri 1 Polewali students. This study used quantitative methods involving 306 students of SMA Negeri 1 Polewali using the Stratified Random Sampling Technique. The data obtained are then analyzed using Simple Regression analysis techniques. The instruments used are school well-being and student engagement measuring instruments. The results of the hypothesis test showed an R-square value of 0.440 (44%). This shows that there is a role for school well-being in student engagement in students. This research can be used as a reference for students and schools to overcome the problem of low student involvement in schools.